Increased genetic vulnerability to smoking at CHRNA5 in early-onset smokers - Hartz, Sarah M.; Frank, Josef; Rawal, Rajesh; Muley, Thomas; Risch, Angela; Rietschel, Marcella (Archives of general psychiatry, 2012)
Context Recent studies have shown an association between cigarettes per day (CPD) and a nonsynonymous single-nucleotide polymorphism in CHRNA5, rs16969968. Objective To determine whether the association between rs16969968 and smoking is modified by age at onset of regular smoking. Data Sources Primary data. Study Selection Available genetic studies containing measures of CPD and the genotype of rs16969968 or its proxy. Data Extraction Uniform statistical analysis scripts were run locally. Starting with 94 050 ever-smokers from 43 studies, we extracted the heavy smokers (CPD >20) and light smokers (CPD ≤10) with age-at-onset information, reducing the sample size to 33 348. Each study was stratified into early-onset smokers (age at onset ≤16 years) and late-onset smokers (age at onset >16 years), and a logistic regression of heavy vs light smoking with the rs16969968 genotype was computed for each stratum. Meta-analysis was performed within each age-at-onset stratum. Data Synthesis Individuals with 1 risk allele at rs16969968 who were early-onset smokers were significantly more likely to be heavy smokers in adulthood (odds ratio [OR] = 1.45; 95% CI, 1.36-1.55; n = 13 843) than were carriers of the risk allele who were late-onset smokers (OR = 1.27; 95% CI, 1.21-1.33, n = 19 505) (P = .01). Conclusion These results highlight an increased genetic vulnerability to smoking in early-onset smokers.
Gesehen am 03.09.2018